Effects of Graphene Oxide Dispersion on Salt-Freezing Resistance of Concrete - Yihong Xu; Yingfang Fan (Advances in Materials Science and Engineering)
In order to study the effects of different amounts of graphene oxide dispersion on the salt-freezing resistance of concrete, graphene oxide lamellar dispersion with a concentration of 5 mg/ml was prepared by the improved Hummers’ method and the ultrasonic dispersion method. Graphene oxide (GO) was characterized by Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The mechanical properties and durability of the salt-frozen concrete with different GO contents were examined, and its salt-freezing resistance mechanism was analyzed by microscopic tests. With the increasing salt-freezing time, the deterioration of GO concrete occurred under a combination of different modes, such as mortar shedding, microcrack propagation, denudation, and massive shedding. The optimum content of GO was detected as 0.03%. In comparison to the reference specimen, the compressive strength of GO concrete increased by 34.83% after 200 salt-freezing cycles, and consequently loss rate and dynamic elastic modulus were found to be the smallest. The microscopic test results revealed the optimum GO content promoted the hydration of cement, regulated its microstructure, effectively hindered the destruction of concrete micromorphology during salt-freezing, and slowed down the initiation and propagation of internal microcracks. Hence, the mechanical and endurance properties of GO concrete were significantly improved after salt-freezing.